環境調整を併用した運動療法が薬原性錐体外路症状を伴う慢性統合失調症者の歩行機能に及ぼす影響について - 四方 公康; 岡崎 信也; 山本 隆一; 木村 保 (理学療法学, 2014)
Purpose: This study was designed to investigate the effects of exercise therapy combined with environmental manipulation on walking function in patients with chronic schizophrenia and drug-induced extrapyramidal symptoms. Subjects: Eighteen patients with chronic schizophrenia complicated by drug-induced extrapyramidal symptoms who were hospitalized in the locked ward of psychiatric hospital C were investigated in this study. Methods: This was a randomized crossover comparative study. Patients were randomly divided into group A (n=10) and group B (n=8). Both groups underwent the same exercise therapy for 4 weeks, following which the presence or absence of significant differences in walking function were determined. Subsequently, without a rest period, group A and group B began exercise therapy with and without environmental manipulation, respectively. Each group switched the exercise regimen after 4 weeks. Results: Significant changes in walking function were observed after the environmental manipulation. In addition, the creation of a performance checklist was the most effective aspect of environmental manipulation. Conclusion: The results of this study suggest that exercise therapy combined with environmental manipulation may be effective in improving the walking function of patients with chronic schizophrenia and drug-induced extrapyramidal symptoms. 【目的】本研究では,環境調整を併用した運動療法が薬原性錐体外路症状を伴う慢性統合失調症者の歩行機能に及ぼす影響について検討した。【対象】C精神科病院閉鎖病棟入院中の薬原性錐体外路症状を合併した慢性統合失調症者18名とした。【方法】ランダムにA群10名とB群8名の2群に分け,両群に同じ内容の運動療法を4週間実施し,その前後の歩行機能に有意差がないことを確認した。その後休止期間は設けず,A群は,環境調整を実施した運動療法を開始し,B群は,環境調整を実施しない運動療法を開始し,4週間後にそれぞれの条件を入れ替える,ランダム化クロスオーバー比較試験により実施した。【結果】環境調整実施前後では,歩行機能に有意な変化を認めた。また,動作確認表の作成が,環境調整の中でもっとも有効であった。【結論】本研究から,環境調整を併用した運動療法が,薬原性錐体外路症状を伴う慢性統合失調症者の歩行機能において,有効である可能性が示唆された。